KONTAK JODOH BERBASIS WEB MOBILE MENGGUNAKAN FRAMEWORK JQUERY MOBILE (Information Technology and Telematics, 2014)
Abstract One thing we cannot at the present time aside this is the development of the technology world. Where systems are constantly evolving pattern of life is the participation of the technological advances continually growing rapidly. matchmaking is often facilitated by the relationship of parents both sides of the family, which match her ​​with her ​​childhood friend, colleague, friend his business, or his best friend, now the world has shifted matchmaking left the old traditions. Based on the review for this is generally a person who follows the online dating want practicality and ease of determining a spouse. people who have a solid rushing up not having time to just join the social communities. Thus of course they also do not have the time to just meet and do an assessment of the opposite sex who takes the time to meet, chat and so forth. They make use of technology that is practical and can be done wherever and whenever they want to use it without having to set aside a special time. Keywords: Contacts mate, Jquery Framework, Mobile Web.